1991
DOI: 10.1002/ajpa.1330850105
|View full text |Cite
|
Sign up to set email alerts
|

Root dentine transparency: Age determination of human teeth using computerized densitometric analysis

Abstract: Root dentine transparency (RDT) was used to estimate the ages of human subjects from 152 intact teeth. Teeth were from 134 subjects, both historical and recent, of known age and sex. The aims of this work are 1) to compare two methods of using RDT to estimate age; 2) to test the applicability of the regression formulae for estimating age obtained from a recent sample on an historical sample; and 3) to estimate the suitability of RDT to determine age at death of 100-year-old skeletons. RDT was measured by two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1
6

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 12 publications
4
50
1
6
Order By: Relevance
“…This shows that these features can be used to estimate age, but that the results would not be highly accurate. Root transparency did not obtain the highest results as was found in previous works [5,[8][9][10][11][12][13][14][15][16] while periodontosis, surprisingly, were found to correlated more with age than root transparency. Hillson [20] also reported that there are large clinical studies that showed a clear relationship between periodontosis and age, and that dental hygiene and care play a big role in the development of periodontal disease.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…This shows that these features can be used to estimate age, but that the results would not be highly accurate. Root transparency did not obtain the highest results as was found in previous works [5,[8][9][10][11][12][13][14][15][16] while periodontosis, surprisingly, were found to correlated more with age than root transparency. Hillson [20] also reported that there are large clinical studies that showed a clear relationship between periodontosis and age, and that dental hygiene and care play a big role in the development of periodontal disease.…”
Section: Discussionmentioning
confidence: 45%
“…As teeth are the most durable of all human remains, much of the efforts have focused on the human dentition, and of particular interest here is the study published in 1992 by Lamendin et al [1]. Dental attrition [2], secondary dentin deposition [3][4][5], and root transparency [6][7][8][9][10][11][12][13][14][15][16] have been among the many characteristics examined.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…치아는 인체 조직 중 가장 오래 보존되고 [10], 골조직과는 달리 구강 내에서 직접적인 관찰이 가능하며 [11], 증령에 따른 변화가 비교적 단계적이어서 개인차가 가장 적게 나타나는 것 으로 알려져 있기 때문에 연령 추정에 유용하다 [3]. 치아를 연령 추정에 이용하는 경우에는 Gustafson 방법 [12], 치근부 상아질 투명도(dentine transparency) [13,14] …”
Section: 고 찰unclassified